From the North Atlantic to the South China Sea Allied Maritime Strategy in the 21st Century - Pawlak, Julian; Peters, Johannes (ISPK Seapower Series, 2021)
This book provides answers on how allies have to prepare for the strategic challenges in the maritime domain of the 21st century. 24 noted international authors, scholars and practitioners alike, refer to areas of operation and relevant trends and developments. They include the strategic consideration of NATO's "Northern Flank" as well as an outlook on "Naval Warfare 4.0". The concise chapters are characterized by their scientific fundament, on which basis recommended actions are drawn. With its substantial practical relevance, this volume is of much value for academics and practitioners in the fields of international relations, security policy, and strategic studies in Germany, Europe, and NATO. With contributions by James H. Bergeron, Keith E. Blount, Sebastian Bruns, Jim Fanell, James Goldrick, Niklas Granholm, Tom Guy, Frank Hoffmann, Sidharth Kaushal, Frédéric Lasserre, Kaspar Pajos, Sarandis Papadopoulos, Chris Parry, Julian Pawlak, Johannes Peters, Pauline Pic, Deborah Sanders, John Sherwood, Dirk Siebels, Jeremy Stöhs, Bruce Stubbs, Sarah Tarry and Alix Valenti.